PO 18191 - Congenital distal tibiofibular diastasis: report of two cases with more than 20 years of follow-up - Maria Pereira, Jordanna; Cardenuto Ferreira, Ricardo; Tulio Costa, Marco; de Marchi Neto, Noé; Kerry Gobbo, Daiana; Cursino Fernandes, Milena Peloggia (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Congenital distal tibiofibular diastasis is an extremely rare entity of unknown etiology that compromises the feet and ankles with different degrees of deformity, although in general, the feet show equinovarus deformity, and the talus is proximally dislocated due to the separation of the distal tibial and fibular epiphyses. There are few reports of this disorder in the literature, and most describe cases that ultimately lead to limb amputation. We present the cases of 2 patients treated from birth to skeletal maturity. Methods: Two female patients with clubfoot at birth were diagnosed with congenital distal tibiofibular diastasis. One of them had the deformity of the right foot, and the other had deformity of both limbs. Both patients underwent early distal tibiofibular arthrodesis and serial stretching of the compromised feet and legs. Results: After 20 years of clinical follow-up and after reaching skeletal maturity, both patients had plantigrade feet without significant shortening of the lower limbs or pain, and both performed activities of daily living without restrictions, wearing conventional shoes. Conclusion: Early distal tibiofibular arthrodesis followed by limb stretching was effective for treating congenital distal tibiofibular diastasis and is a good alternative to amputation, which is indicated in the literature.